P189 Role of digestive wall's ultrasound in the evaluation of post-surgical recurrence in Crohn's disease: correlation with endoscopic findings. (25th January 2019) - Macedo, C; Gravito-Soares, E; Gravito-Soares, M; Ferreira, A M; Portela, F; Tomé, L
Abstract: Background: Endoscopy remains the examination of choice in the evaluation of activity in Crohn's Disease (CD) after surgery (ADC-AS). However, digestive wall's ultrasound (US-DW) may represent a non-invasive alternative. The objective of this study was to determine the diagnostic accuracy and concordance of this modality comparatively to endoscopy. Methods: Cross-sectional study, comprising a period of 14 months, carried out in patients with established CD and ileocaecal resection due to the disease. Performed US-DW (HI-VISION avius®, Tokyo, Japan) with linear probe B-mode/Doppler prior to ileocolonoscopy. US-DW and colonoscopy were performed on the same day by 2 specialists in gastroenterology dedicated to ultrasound and inflammatory bowel disease, in a double-blind mode. Collected demographic and clinical data [Harvey–Bradshaw index (HBI, remission: ≤4)], serological/faecal inflammatory parameters [leucocytes (4 < N <10 × 10 9 cells/l), C-reactive protein (≤0.5 mg/dl) faecal calprotectin ( N <50 mg/kg), endoscopic (score Rutgeerts: remission < i2) and ultrasound [intestinal wall thickening ( N ≤ 3 mm) and digestive wall's vascularisation using the semi-quantitative score of Limberg (absent = 0, sparse = 1; moderate = 2; marked = 3)]. Results: Included 39 patients (female: 64.1%, mean age: 43.5 ± 15.3 years). Surgery performed, on average, 5.3 ± 5.3 years after diagnosis. Mean post-surgery follow-up: 9.9 ± 6.9 years. Montreal classification: L1 61.5% ( n = 24), L3 38.5% ( n = 15), B1 and B2 28.2% ( n = 11) and B3 43.6% ( n = 17). Most of patients were in clinical remission (87.2%; n = 34) with mean HBI 2.1 ± 2.2. Twenty-two patients (56.4%) have normal inflammatory markers. US-DW (intestinal wall thickening> 3 mm and/or Limberg> 1) was abnormal in 61.5% ( n = 24). Endoscopic remission (Rutgeerts <i2) in 53.8% ( n = 21). Comparatively to endoscopy, the US-DW (AUROC 0.81; p = 0.001) showed a diagnostic accuracy superior to the inflammatory parameters (AUROC = 0.66; p = 0.083) and clinic (AUROC 0.64; p = 0.13). Ultrasonography showed good endoscopic concordance (Kappa 0.6, p = 0.001), higher than the inflammatory parameters (Kappa 0.33, p = 0.04) and clinic (Kappa 0.3, p = 0.01). Conclusions: The ultrasound evaluation of the digestive wall showed a good diagnostic accuracy and a good concordance with endoscopic, superior to clinical and inflammatory parameters.